Cors Caron - James, Meleri Wyn (Y Lolfa, 2022)
A mystery novel for children set against the backdrop of the Caron marshland in mid-Wales. The story moves swiftly between two worlds, and deals with themes of relationship, love and the change in our attitude towards the environment.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books